Body-related embarrassment: The overlooked self-conscious emotion. (March 2020) - Vani, Madison F.; Pila, Eva; Willson, Erin; Sabiston, Catherine M.
Highlights: Body-related embarrassment often occurred in the presence of others. Contexts primarily included school and physical activity or sport settings. Body-related embarrassment is a key additional self-conscious emotion to study. Abstract: Embarrassment is an understudied self-conscious emotion both experienced globally and in the context of the body. Drawing from affective body image tenets, this investigation aimed to better understand body-related embarrassment in a final sample of 187 adolescent and young adult males and females. A thematic content analysis was used to analyze self-report narratives from a relived emotion task and participants completed a self-report survey about the social environmental features of the emotional experience. Seven first-order themes and twenty-two second order themes were identified. Contexts for experiences of body-related embarrassment primarily included school, swimming pool/beach, sport and non-sport change rooms, and other sport or physical activity settings. Body-related embarrassment most often occurred when five or more individuals were present. Antecedents included fear of or actual negative evaluation, social comparisons, body exposure, and inadequacy compared to an internal standard. Outcomes included affective states and cognitive (e.g., avoidance) and behavioral (e.g., appearance management) outcomes. Compared to females, males reported less self-consciousness and were less likely to experience embarrassment around the other gender. Understanding the elicitation and experience of different emotions such as body-related embarrassment can guide theory and practice and may help to develop specific and unique interventions to address differing emotions.